2019
DOI: 10.1016/j.crad.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification is associated with mortality independent of pulmonary embolism severity: a retrospective cohort study

Abstract: To assess coronary artery calcification (CAC) and vascular calcification in patients with pulmonary embolism (PE) and correlate this with mortality. MATERIALS AND METHODS: PE severity was quantified using computed tomography pulmonary angiography (CTPA) in 400 consecutive cases using the modified Miller score (1e5, mild; 6e11, moderate; 12e16, severe). Right ventricle strain was assessed using the right/left ventricle diameter (RV/LV) ratio. CAC score (CACS) was assessed using a four-point scale (CACS mild 1e3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Coronary artery calcification is a frequent incidental finding on CTPA, however radiologists infrequently report CTPA coronary artery calcification score when reporting scans performed for the investigation of suspected PE [ 4 , 21 ]. Williams et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronary artery calcification is a frequent incidental finding on CTPA, however radiologists infrequently report CTPA coronary artery calcification score when reporting scans performed for the investigation of suspected PE [ 4 , 21 ]. Williams et al .…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al . have recently reported that the presence of coronary artery calcification identified on CTPA is a more important predictor of all-cause 3-year mortality than the severity of PE [ 21 ]. In their cohort, patients with severe calcification were reported to be almost five-times more likely to die at 3-years when compared to patients without coronary artery calcification [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing CT for suspected PE are more likely to have coronary artery calcifications [38]. Few studies in the literature have investigated the importance of coronary artery calcifications on both short-and long-term mortality in patients with APE [39,40]. Ng et al, in their study of 1023 patients diagnosed with PE, showed that long-term all-cause cardiovascular mortality was 2.2 higher than in patients without cardiovascular diseases [41].…”
Section: Coronary Artery Calcificationsmentioning
confidence: 99%
“…Recommendations for the assessment of cardiac calcification on routine thoracic CT Coronary artery calcification on non-gated thoracic CT CAC can be identified on non-gated thoracic CT with an excellent diagnostic accuracy compared to gated CT. 25,26 However, CAC is frequently not reported on non-gated thoracic CT, [27][28][29][30] and a recent survey demonstrated only 17% of noncardiothoracic radiologists in Canada were aware of the correlation between CAC scores on gated and non-gated thoracic CT. 31 The incidence of CAC on non-gated thoracic CT performed for non-cardiac indications varies from 26 to 93% depending on the population assessed. [28][29][30][32][33][34] It is associated with poorer prognosis in a variety of patient cohorts including patients with chronic obstructive pulmonary disease, pulmonary embolism, cancer and in unselected patients undergoing thoracic CT. 32,[35][36][37][38][39] In the National Lung Screening Trial, CAC was associated with an increased risk of coronary artery disease-related death, with a CAC score of 100-1000 AU associated with a fourfold increase, and CAC score of >1000 AU associated with a sevenfold increase compared to patients without CAC. 35 Reporting coronary calcification While conventional Agatston scoring remains the gold-standard assessment, it requires dedicated software and training.…”
Section: Coronary Artery Calcificationmentioning
confidence: 99%